The interaction between conventional monetary policy and financial stability : Chile, Colombia, Japan, Portugal and the UK - Venter, Zoë (2019)
The relationship between monetary policy and financial stability has gained importance in recent years as Central Bank policy rates neared the zero-lower bound. The need to coordinate policy choices, to expand the scope of monetary policy measures and lastly, the need to target financial stability objectives while maintaining a primary objective of financial stability, has become essential. We use an SVAR model and impulse response functions to study the impact of monetary policy shocks on three proxies for financial stability as well as a proxy for economic growth. Our main results show that the Central Bank policy rate may be used to correct asset mispricing due to the inverse relationship between the policy rate and the stock market index. The results also show that, in line with theory, the exchange rate appreciates following a positive interest rate shock. Although the impact is only statistically significant for industrial production for the case of the UK, conventional monetary policy may indeed be able to contribute to financial stability when used in conjunction with alternative policy choices.